The Life History and Distribution of Etmopterus spinax in Icelandic Waters - Helga Mattína Sveinsdóttir 1998- (2022)
Sharks are exceptionally vulnerable to extinction, as their life histories are characterized by slow growth rates, late sexual maturity, low fecundity, and long lifespans. Deep-sea sharks are even more vulnerable to overfishing than other shark species, as their life histories are even less productive than for other groups of sharks. And still, not much is known on the intricacies of the life histories of many deep-sea sharks. The velvet belly lanternshark (Etmopterus spinax) is a small, bioluminescent shark found in Icelandic waters and is commonly caught as bycatch in many deep-sea fisheries in the Atlantic Ocean. Little is known about E. spinax in Icelandic waters, as most studies on the species have been conducted in the northeastern Atlantic Ocean and in the Mediterranean Sea. Using data provided by the Marine and Freshwater Research Institute, the life history and distribution of E. spinax in Icelandic waters was studied for the first time. The distribution range of E. spinax in Icelandic waters is primarily bound to waters in the southwest of Iceland. Females were considerably larger than males and reached maturity at larger sizes. Etmopterus spinax in Icelandic waters are substantially larger than previously reported maximum lengths, the biggest sample in this study being 66 centimeters in total length. This research project will be the first to look into the life history and long-term distribution of E. spinax in Icelandic waters, increasing the knowledge on deep-sea sharks found in Iceland and the northern Atlantic Ocean.